(untitled) (REMUNOM, 2024)
Historically, deaf people have been struggling for many years. Since the Ancient Age, they were considered by the Egyptian peoples to be people sent by the gods, privileged people, and they were also considered to be beings of innate life and did not have the right to education. In this article we seek to provide a social history of this individual, as would be their historical journey as a social subject. We have identified the first book on deaf education that described the manual alphabet, published by Juan Pablo Bonet in the mid-1620s, in the work “Reduccion delas letras y arte para ensiñar a hablar los mudos”. In this book, the author demonstrates the oral method that was used as a basis for teaching throughout Europe, as Veloso and Maia (2017) point out. The theoretical-methodological approach to this article was qualitative, based on bibliographical research by authors such as Lacerda (2012) and Strobel (2018), among others. The locus of the research was the Municipal Bilingual Children’s School of Porto Velho-RO.